Penguatan Karakter Calon Karyawan melalui Khuruj fi Sabililllah di Lembaga Pendidikan dan Pengembangan Profesi Indonesia Surabaya - Darmawan, Agus (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2023)
This article will discuss strengthening the Divine character of prospective employees who are pursuing professional education at the Surabaya Professional Education and Development Institute (LP3I) through Khuruj fi Sabilillah. The aim of this research is to determine the extent of Khuruj fi Sabilillah's effectiveness in instilling Islamic religious values ​​for prospective employees who are preparing to become professional employee candidates who have good quality soft skills through a 2 year professional education program at LP3I Surabaya. To obtain the author's data, data collection in this research was carried out through literature study to determine the concepts of Khuruj fi Sabilillah and strengthening Divine character as well as through observation, interviews and documentation to determine the implementation of Khuruj fi Sabilillah in strengthening Divine character. From the data analysis carried out by the author, it was found that strengthening soft skills for prospective employees pursuing professional education can be carried out by cultivating the Divine nature, because the Divine nature contains noble values ​​that strengthen the quality of soft skills. The cultivation of the Divine nature into the Divine character can be carried out effectively through the implementation of Khuruj fi Sabilillah because in the implementation of Khuruj fi Sabilillah the Divine nature is not only understood to the congregation through ta'lim wa taklum but is also practiced in the form of amaliyah and preached. Having a strong Divine character as a supporting factor for the quality of hard skills opens up opportunities for prospective employees to get better opportunities in the employee recruitment process and building a career. It is hoped that the results of this research can provide an effective alternative method for strengthening character in Islamic Religious Education and at the same time become material for developing subsequent research with relevant themes.